ROMPI Si Gigi game media as an effort to improve knowledge and tooth brushing skills of preschool children - Saharani, Adilla; Widiyastuti, Rini (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: In general, learning while playing is popular among children, especially kindergarten students, besides being interesting, children do not get bored easily. To improve knowledge and motivation to learn, one of them is by playing the ROMPI Si Gigi media game. The material in this media is shaped like a spinning wheel and is equipped with pictures of the steps for brushing teeth. Objective: To analyze knowledge and skills before and after being given education on how to brush teeth through the ROMPI Si Gigi game media in preschool children. Method: This research employs a quasi-experimental method with a one-group pretest-posttest design. It was conducted at TK Bakti Mulya 400 South Jakarta, using a purposive sampling technique of 36 respondents. The independent variable is the ROMPI Si Gigi game media and the dependent variable is the knowledge and skills of brushing teeth. The instruments are in the form of questionnaire sheets (pretest and posttest), checklist sheets for brushing teeth skills. Results: This study shows that the results of respondents' knowledge before the ROMPI Si Gigi media game education were mostly in the sufficient criteria of 18 students (50.0%) and after being given education, most were in the good criteria of 21 students (58.4%). Respondents' skills before the ROMPI Si Gigi media game education were mostly in the sufficient criteria of 14 students (38.9%) and after education, most were in the very good criteria of 36 students (100%). Conclusion: There was an increase in knowledge and skills in brushing teeth after being given ROMPI Si Gigi media game education.